Zika virus disrupts the barrier structure and Absorption/Secretion functions of the epididymis in mice. - Ziyang Sheng; Na Gao; Dongying Fan; Na Wu; Yingying Zhang; Daishu Han; Yun Zhang; Weilong Tan; Peigang Wang; Jing An (Public Library of Science (PLoS), 2021)
Several studies have demonstrated that Zika virus (ZIKV) damages testis and leads to infertility in mice; however, the infection in the epididymis, another important organ of male reproductive health, has gained less attention. Previously, we detected lesions in the epididymis in interferon type I and II receptor knockout male mice during ZIKV infection. Herein, the pathogenesis of ZIKV in the epididymis was further assessed in the infected mice after footpad inoculation. ZIKV efficiently replicated in the epididymis, and principal cells were susceptible to ZIKV. ZIKV infection disrupted the histomorphology of the epididymis, and the effects were characterized by a decrease in the thickness of the epithelial layer and an increase in the luminal diameter, especially at the proximal end. Significant inflammatory cell infiltration was observed in the epididymis accompanied by an increase in the levels of interleukin (IL)-6 and IL-28. The expression of tight junction proteins was downregulated and associated with disordered arrangement of the junctions. Importantly, the expression levels of aquaporin 1 and lipocalin 8, indicators of the absorption and secretion functions of the epididymis, were markedly reduced, and the proteins were redistributed. These events synergistically altered the microenvironment for sperm maturation, disturbed sperm transport downstream, and may impact male reproductive health. Overall, these results provide new insights into the pathogenesis of the male reproductive damage caused by ZIKV infection and the possible contribution of epididymal injury into this process. Therefore, male fertility of the population in areas of ZIKV epidemic requires additional attention.